The Robotic Reporter in The Czech News Agency: Automated Journalism and Augmentation in the Newsroom - Moravec, Václav; Macková, Veronika; Sido, Jakub; Ekštein, Kamil (Communication Today, 2020)
The use of automated journalism, also known as robotic journalism or artiﬁcial intelligence journalism, became an established practice in English-speaking countries less than ten years ago. Narrative Science and Automated Insights developed creative software that automatically generates reports. Several media outlets, including The Associated Press (AP), have started to publish their reports. Media landscape barriers based on Slavic languages, such as Czech, have caused some delays in the introduction of automated journalism, or artiﬁcial intelligence journalism, in Central and Eastern Europe. This article is a case study of the application of algorithms that transform large data ﬁles into news texts in The Czech News Agency (ČTK). A research team led by Charles University provided algorithms generating reports on trading results on the Prague Stock Exchange without human intervention to The Czech News Agency in 2019. The study deals with the production of algorithms and compares the rate of generation of messages generated by humans against algorithms and examines their quality. In our research we also used observations and questionnaire surveys of selected journalists and editors who work with reports from the Prague Stock Exchange. The article also provides the opinions of journalists of The Czech News Agency on the application of automated journalism and artiﬁcial intelligence journalism in their newsrooms.